Synthesis and Characterization of Polyvinyl Alcohol-Gum Arabic Polymer Blend Membranes - Jayan, Larny Mary; Karthikeyan, S.; Sheeba, D. Joice; Angel, G.R.; Kripa, E.V.; Madeswaran, S.; Stephen, A. (Asian Journal of Chemistry, 2019)
Membranes of poly(vinyl alcohol) (PVA), gum arabic (GA) homopolymer and their blends of six different compositions (w/w) were prepared using solution casting method. Mixing of synthetic polymer e.g., PVA and natural polymer e.g., gum arabic can give a new class of polymer blend with better mechanical properties and biocompatibility than those of single components. The structural, optical and conductivity studies of these prepared membranes were examined by XRD, FTIR, UV and EIS. The XRD diffraction patterns for the polymer blend samples showed that they are more amorphous in nature as compared to pure PVA and pure gum arabic. The FTIR analysis of the samples gave information about various functional groups present in the samples. The energy band gap of various samples were obtained from UV-visible analysis. The conductivity of polymer membrane was analyzed by electronics impedance spectroscopy (EIS). Addition of natural polymer gum arabic has resulted slight increase in the conductivity of blend polymer.